(untitled) (Caring: Indonesian Journal of Nursing Science, 2025)
Nurses’ motivation is a critical determinant of quality of care, professional engagement, and workforce retention. While self-leadership and caring leadership have been widely examined as separate constructs, the integration of caring values into self-leadership practices referred to here as caring-based self-leadership has not been systematically synthesized. This systematic review aims to identify, evaluate, and synthesize empirical evidence on caring-based self-leadership and its relationship with nurse motivation in hospital settings. Acomprehensive literature search was conducted in PubMed, Scopus, ScienceDirect, CINAHL, and Google Scholar for peer-reviewed articles published between 2015 and 2025 in English or Indonesian. The review followed PRISMA 2020 guidelines, and methodological quality was appraised using the Joanna Briggs Institute (JBI) critical appraisal tools. A total of 1,245 records were identified; 132 full-text articles were assessed, and 17 studies met the inclusion criteria. Three main themes emerged: (1) self-leadership enhances intrinsic motivation through self-regulation and goal setting; (2) caring or engaging leadership provides organizational support that strengthens nurses’ motivation; and (3) psychological and organizational mediators/moderators (e.g., job resources, calling, affective commitment) shape these relationships. Substantial heterogeneity was observed across study design, measures and cultural contexts. Caring-based self-leadership promotes nurses’ intrinsic motivation and engagement through cognitive, emotional, and organizational mechanisms, offering a humanistic foundation for leadership development and quality improvement in nursing practice. Keyword: Self-leadership, Caring Leadership, Nurse Motivation, Intrinsic Motivation